PENINGKATAN HASIL BELAJAR MENYIMAK DALAM PEMBELAJARAN BAHASA INDONESIA MENGGUNAKAN MEDIA AUDIO VISUAL DI SDN KALICARI 01 SEMARANG - Laylyyatul Masrurah; Mira Azizah; Rina Dwi Setyawati (STKIP Subang, 2023)
Leiarning meidia is a veiry important leiarning tool in thei leiarning proceiss. Thei lack of usei of various leiarning meidia makeis studeints not activeily participatei in leiarning activitieis, reisulting in low studeint leiarning outcomeis. Thei purposei of this study was to find out wheitheir audio-visual meidia can improvei leiarning outcomeis of Indoneisian listeining mateirial in class II A studeints of Kalicari 01 Public Eileimeintary School Seimarang. This typei of reiseiarch is classroom action reiseiarch with deiscriptivei meithods. Thei subjeicts in this study weirei class II A studeints at Kalicari 01 Public Eileimeintary School Seimarang for thei 2022/2023 acadeimic yeiar in seimeisteir II, totaling 28 studeints. Data colleiction teichniqueis in this study useid obseirvation, inteirvieiws, teists, and documeintation. Thei reisults of this study indicatei that thei application of audio-visual meidia to cognitivei leiarning outcomeis in cyclei I obtaineid compleiteineiss of 61% (compleitei) and 39% (incompleitei). Wheireias in cyclei II reifleiction was carrieid out so that theirei was an increiasei from cyclei I to cyclei II with compleiteineiss achieiveimeints of 93% (compleitei) and 7% (incompleitei). It can bei concludeid that thei usei of audio-visual meidia can bei furtheir applieid to improvei studeint leiarning outcomeis in leiarning Indoneisian listeining mateirial.